Quantum sensitivity limits of nuclear magnetic resonance experiments searching for new fundamental physics. (15th June 2021) - Aybas, Deniz; Bekker, Hendrik; Blanchard, John W; Budker, Dmitry; Centers, Gary P; Figueroa, Nataniel L; Gramolin, Alexander V; Jackson Kimball, Derek F; Wickenbrock, Arne; Sushkov, Alexander O
Abstract: Nuclear magnetic resonance is a promising experimental approach to search for ultra-light axion-like dark matter. Searches such as the cosmic axion spin-precession experiments (CASPEr) are ultimately limited by quantum-mechanical noise sources, in particular, spin-projection noise. We discuss how such fundamental limits can potentially be reached. We consider a circuit model of a magnetic resonance experiment and quantify three noise sources: spin-projection noise, thermal noise, and amplifier noise. Calculation of the total noise spectrum takes into account the modification of the circuit impedance by the presence of nuclear spins, as well as the circuit back-action on the spin ensemble. Suppression of the circuit back-action is especially important in order for the spin-projection noise limits of searches for axion-like dark matter to reach the quantum chromodynamic axion sensitivity.